Pengaruh Kepemimpinan Transformasional, Komitmen Organisasi dan Motivasi Kerja terhadap Kinerja Pegawai pada Perusahaan Daerah Air Minum (PDAM) Amuntai Kabupaten Hulu Sungai Utara - Humaidi Humaidi; Emy Rahmawati; Irwansyah Irwansyah (JURNAL BISNIS DAN PEMBANGUNAN, 2019)
An organization or a company must be able to manage its management to win the competition in an all-competitive era in order to survive to grow and develop in accordance with company goals. Every organization always has problems on human resources. Therefore, with the existence of the problem, it is necessary to have a leader who has transfrormational leadership patterns so that problems within the company can be resolved. In addition to improving the performance of employees within the company, organizational commitment and high work motivation are needed in order to achieve and fulfill company goals well.This study aims to examine the influence of Transformational Leadership (X1), Organizational Commitment (X2) and Work Motivation (X3) on Employee Performance (Y) at Perusahaan Daerah Air Minum (PDAM) Amuntai Kabupaten Hulu Sungai Utara, either partially or simultaneously. Samples were taken as many as 67 employees using saturated sampling technique. Data collection using questionnaire while data analysis using Multiple Linear Regression Analysis through SPSS program version 23.00The test result proves that Trasnformational Leadership had a significant effect on Employee Performance partially with the influence of 81,1% including very strong category, Organizational Commitment has significant influence to Employee Performance partially with big influence 44,3% including strong enough category, Work Motivation has significant effect to Performance Employees partially with a large influence of 61.9% including strong category while simultaneously Leadership Trasformasional, Organizational Commitment and Work Motivation significant effect on Employee Performance with a large influence 88.4% including very strong category while the remaining 11.6% influenced by another variable.  Keywords: Transformasional Leadership, Organizational Commitment, Motivation Employment and Employee Performance